Effective Activation and Expansion of Canine Lymphocytes Using a Novel Nano-Sized Magnetic Beads Approach - Szopa, Iwona Monika; Granica, Monika; Bujak, Joanna Katarzyna; Łabędź, Agata; Błaszczyk, Maciej; Paulos, Chrystal Mary; Majchrzak-Kuligowska, Kinga (Frontiers in Immunology, 2021)
Expansion protocols for human T lymphocytes using magnetic beads, which serve as artificial antigen presenting cells (aAPCs), is well-studied. Yet, the efficacy of magnetic beads for propagation and functionality of peripheral blood lymphocytes (PBLs) isolated from companion dogs still remains limited. Domestic dog models are important in immuno-oncology field. Thus, we built the platform for induction of canine PBLs function, proliferation and biological activity using nano-sized magnetic beads (termed as MicroBeads) coated with anti-canine CD3 and CD28 antibodies. Herein we reveal that activation of canine PBLs via MicroBeads induces a range of genes involved in immediate-early response to T cell activation in dogs. Furthermore, canine T lymphocytes are effectively activated by MicroBeads, as measured by cluster formation and induction of activation marker CD25 on canine T cells as quickly as 24 hours post stimulation. Similar to human T cells, canine PBLs require lower activation signal strength for efficient proliferation and expansion, as revealed by titration studies using a range of MicroBeads in the culture. Additionally, the impact of temperature was assessed in multiple stimulation settings, showing that both 37°C and 38.5°C are optimal for the expansion of canine T cells. In contrast to stimulation using plant mitogen Concanavalin A (ConA), MicroBead-based activation did not increase activation-induced cell death. In turn, MicroBeads supported the propagation of T cells with an effector memory phenotype that secreted substantial IL-2 and IFN-γ. Thus, MicroBeads represent an accessible and affordable tool for conducting immunological studies on domestic dog models. Similarities in inducing intracellular signaling pathways further underscore the importance of this model in comparative medicine. Presented herein MicroBead-based expansion platforms for canine PBLs may benefit adoptive immunotherapy in dogs and facilitate the design of next-generation clinical trials in humans.